PENGARUH SUMBER BAHAN ORGANIK TERHADAP KANDUNGAN KIMIA PUPUK BOKASHI DI KABUPATEN SIKKA: STUDI LABORATORIUM - Yuyun Wahyuni; Yovita Yasintha Bolly; Oktaviana Rosario Sere Gili (Fakultas Pertanian, Universitas Nusa Nipa, 2023)
A study was conducted at the Laboratory of the Faculty of Agriculture, Nusa Cendana University, Kupang, with the aim of determining the macro- and micronutrient contents of the bokashi produced. The results showed that solid organic fertilizer made from gamal leaves contained 33.14% C-organic, 2.10% N, 0.22% P, and 2.15% K. Bokashi made from kirinyuh leaves contained 32.50% C-organic, 2.01% N, 1.10% P, and 2.17% K. Meanwhile, bokashi derived from lamtoro leaves contained 32.02% C-organic, 2.13% N, 0.20% P, and 2.06% K. Bokashi produced from a mixture of kirinyuh, gamal, and lamtoro leaves contained 30.78% C-organic, 2.05% N, 1.12% P, and 2.12% K. In addition to macronutrients, the study also identified micronutrient contents in the solid organic fertilizer. Bokashi made from gamal leaves contained 72.05 ppm Mn, 10.23 ppm Fe, 2.30 ppm Cu, and 5.83 ppm Zn, with a pH of 7.87 and a C/N ratio of 15.78. Bokashi from kirinyuh leaves contained 24.13 ppm Mn, 9.01 ppm Fe, 2.80 ppm Cu, and 7.86 ppm Zn, with a pH of 9.19 and a C/N ratio of 16.17. Bokashi from lamtoro leaves contained 20.77 ppm Mn, 11.78 ppm Fe, 3.35 ppm Cu, and 6.44 ppm Zn, with a pH of 8.99 and a C/N ratio of 15.03. Meanwhile, bokashi made from a mixture of kirinyuh, gamal, and lamtoro leaves contained 30.98 ppm Mn, 10.12 ppm Fe, 2.75 ppm Cu, and 6.10 ppm Zn, with a pH of 9.09 and a C/N ratio of 15.02.